2019
DOI: 10.21315/mjms2019.26.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Wii Balance Board for Static Balance Assessment in Healthy Young Adults

Abstract: Introduction The Wii Balance Board (WBB) is a commonly used tool for balance assessment, however the inconsistency in the reported validity for the WBB when used for the assessment of healthy young adults needs to be clarified. Aim To investigate the concurrent validity and reliability of the WBB for balance assessment in healthy young adults. Methods Thirty-two young adults participated in this study. Their ability to balance was tested whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The Wii Balance Board (WBB) is a commonly used balance assessment tool, but it needs to be clarified that the WBB has reported inconsistent validity when used to assess healthy young adults. Kaewkaen et al explore the concurrent validity and reliability of the WBB in the assessment of balance in healthy young adults [ 1 ]. The purpose of Hamed et al's study was to evaluate the effectiveness of specific exercise interventions that control mechanisms of dynamic postural stability in older adults under unstable conditions [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Wii Balance Board (WBB) is a commonly used balance assessment tool, but it needs to be clarified that the WBB has reported inconsistent validity when used to assess healthy young adults. Kaewkaen et al explore the concurrent validity and reliability of the WBB in the assessment of balance in healthy young adults [ 1 ]. The purpose of Hamed et al's study was to evaluate the effectiveness of specific exercise interventions that control mechanisms of dynamic postural stability in older adults under unstable conditions [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies had demonstrated WBB's validity in static balance [7,31,33,34]. Clark et al [7] and Park et al [35] used a laboratory-grade FP to demonstrate WBB's validity in healthy people with ICC ranging from 0.731 to 0.89.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the advent of a portable force platform designed for an electronic games -the WBB, becomes a potential complement of the FP to meet the clinical needs of objective and quanti ed balance assessments. However, most of the previous studies investigated the validation of the WBB in static balance assessment [7,[30][31][32], and there is no previous valid studies about dynamic balance assessment comparing WBB with the laboratory-grade force platform.…”
Section: Discussionmentioning
confidence: 99%
“…Many pieces of research have tested and proved the Nintendo Wii Fit Balance Board (WBB) as an appropriate low-cost device that meets medical standards in both validity and reliability [27][28][29]. Additionally, the device also has the special characteristic that it is easy to move to different areas.…”
Section: Proposed Measurement Devicementioning
confidence: 99%